Relapsing intracranial Rosai-Dorfman disease. Issue 4 (1st October 2001) - Petzold, A; Thom, M; Powell, M; Plant, GT
Abstract : Two patients presenting with recurrent visual impairment due to relapsing intracranial Rosai-Dorfman disease are described. In both patients a preoperative diagnosis of meningioma was made. Histological examination disclosed the characteristic picture of S100 and CD68 positive histiocytosis with prominent lymphophagocytosis. In both patients complete tumour removal by surgery was impossible with residual tissue being the origin of relapsing disease. Low dose radiation led to partial recovery of vision and resolution of the intracranial mass. Review of the literature on intracranial Rosai-Dorfman disease leads to the suggestion that postoperative radiotherapy may be advisable in all cases.